Principles and practice of constraint programming : 22nd International Conference, CP 2016, Toulouse, France, September 5-9, 2016, Proceedings /: 22nd International Conference, CP 2016, Toulouse, France, September 5-9, 2016, Proceedings. (2016) - Unknown
No abstract available